Pediatric postoperative opioid prescribing and the opioid crisis. Issue 3 (June 2019) - Harbaugh, Calista M.; Gadepalli, Samir K.
Abstract : Purpose of review: The purpose of this review is to explore the effects of the opioid crisis on pediatric patients in the postoperative setting and provide recommendations for well-tolerated opioid prescribing practices. Recent findings: Opioid overdoses have increased among all age groups, predominantly related to overprescribing and accessibility of opioids in the home. Adverse risks of prescribed opioids include respiratory depression, gastrointestinal distress, accidental ingestion, intentional misuse, new chronic use, diversion to another user, and overdose. Well-tolerated opioid prescribing practices include multimodal pain management; prescribing guided by patient need; risk assessment for potential misuse; and comprehensive patient and family education on risks, safe storage, and disposal practices. Evolving state laws will affect varying institutional policies; thus, providers must ensure their prescribing practices are current and compliant. Summary: All age groups have been affected by the opioid crisis, including children and adolescents. When managing postoperative pain, clinicians must balance appropriate pain management with well-tolerated opioid stewardship to minimize harm related to postoperative care.